Implementing Google Earth to Enhance Student’s Engagement and Learning Outcome in Geography Learning - Ebid Rocky Alfatikh; Elizabeth Titiek Winanti; Sukma Perdana Prasetya; Eko Budiyanto (Geosfera Indonesia, 2020)
This study aims to examine the effects of Google Earth on students’ engagement in learning and their learning outcome. This study employed pre-experimental design with the One-Shot Case Study design. From the exploration directed crosswise over various areas of evaluation of 12 students in the school, it is demonstrated that dynamic learning of students in was high since it was above 75% and learning outcomes reached an average of 80. This is good considering that the passing grades set in the school was 70. The application of experiential learning methods can produce satisfactory output when viewed from student participation. By looking at the characteristics of schools where students number was less than 20, the teacher is required to develop innovative learning methods. If implemented, this may yield in the improving circumstance of the currently marginalised Geography. Keywords: Google Earth; Student`s activities; Geography learning. Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License